Traylinggwal na diksyunaryong pang-masscom : English-Filipino-Hiligaynon - 4 0 16; Panrehiyong Sentro sa Wikang Filipino.;Rehiyon VI. 5 Philippines (Lungsod ng Iloilo : Komisyon sa Wikang Filipino, 2002)
English-Tagalog-Hiligaynon dictionary of mass communication terms.
Tagalog, Hiligaynon and English.
Keywords: 2 -- 0; 6; Tagalog.;Hiligaynon. -- English language;English language -- 20 -- Dictionaries;Dictionaries; 20; 2